Simulation of Translational Data Acquisition Scheme of X-Ray Computed Tomography for Application in NDT; Key Engineering Materials; Vol. 769 : High Technology: Research and Applications (HTRA 2017) - Afornu B. K. Bright Kwame; Odii Christopher Joseph; Ozdiev A. H. Ali Hosenovich; Sednev D. A. Dmitry Andreevich (2018, 2018)
Title screen